2019
DOI: 10.1186/s10195-019-0538-y
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb lengthening over an intramedullary nail: a long-term follow-up study of 28 cases

Abstract: Background Limb lengthening using an external fixator requires a long period of external fixation and may be associated with several complications such as axial deformity, fracture of the regenerated bone, and joint stiffness. With the goal of reducing the time of external fixation as well as some of these complications, we performed femoral or tibial lengthening over an intramedullary nail, according to Paley’s technique, in 28 patients, followed up after a mean period of 8 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…The principles of the osteogenesis distraction bonded traditionally with the external fixators, considering both monolateral and circular fixators[ 6 , 7 ]. More recently, the deployment of fully implantable systems for limb lengthening has allowed overcoming external fixator-related severities such as pin-site infections, soft tissue tethering, and patient device intolerance during treatment, to name a few[ 8 - 10 ]. Intramedullary nails were initially used in conjunction with external fixation in hybrid techniques such as lengthening over nail or lengthening and then nailing[ 11 , 12 ], in order to reduce fixator time and prevent secondary deformities.…”
Section: Introductionmentioning
confidence: 99%
“…The principles of the osteogenesis distraction bonded traditionally with the external fixators, considering both monolateral and circular fixators[ 6 , 7 ]. More recently, the deployment of fully implantable systems for limb lengthening has allowed overcoming external fixator-related severities such as pin-site infections, soft tissue tethering, and patient device intolerance during treatment, to name a few[ 8 - 10 ]. Intramedullary nails were initially used in conjunction with external fixation in hybrid techniques such as lengthening over nail or lengthening and then nailing[ 11 , 12 ], in order to reduce fixator time and prevent secondary deformities.…”
Section: Introductionmentioning
confidence: 99%
“…They did not observe significant differences in clinical outcomes between the study groups (p = 0.37) but emphasized its advantages of lengthening over an intramedullary nail in the decrease in the duration of external fixation, protection against refracture, and earlier rehabilitation. Using this combined technique, the other authors confirmed its usefulness in the lengthening of the femur and tibia, although the rate of deep infections remains high, from 2.4% to 15% [30][31][32].…”
Section: Discussionmentioning
confidence: 75%
“…and Tjernström et al . reported intraoperative blood loss ranging from 150 to 600 ml using traditional treatment procedures 22 , 23 . In the present study, the mean intraoperative blood loss volume was significantly lower at 53.58 ± 22.51 (range, 25–87) ml.…”
Section: Discussionmentioning
confidence: 99%